Deadly Thought: Hamlet and the Human Soul - Blits, Jan H. (Lexington Books, 2001)
The human soul is for pre-modern philosophers the cause of both thinking and life. This double aspect of the soul, which makes man a rational animal, expresses itself above all in human action. Deadly Thought: 'Hamlet' and the Human Soul traces Hamlet's famous inability to act to his inability to hold together these twin aspects of the soul. Combining careful attention to detail and interpretive breadth, noted scholar Jan H. Blits deftly illustrates how Hamlet collapses life into thought, and moral action into stage acting, and ultimately comes to see his own life as a stage play. Hamlet, the book demonstrates, epitomizes the intellectualism of the Renaissance and the modern age it began, and so becomes tragedy's first self-conscious protagonist, signaling the end of ancient tragedy. Erudite, innovative, and lively, Deadly Thought is a ground-breaking contribution that will appeal to Shakespeare scholars, political theorists, historians of philosophy, literary theorists and anyone interested in a truly fresh interpretation of this classic work.